IoT-Based Electrical Power Consumption Monitoring System in Households Using ESP32 and PZEM-004T - Kemas Muhammad Wahyu Hidayat; Muhammad Ghozi Al-Faris (Brilliance: Research of Artificial Intelligence, 2025)
Electricity consumption in the household sector is often poorly controlled, leading to energy waste and increased electricity bills. To address this issue, this study presents the design and implementation of an electricity consumption monitoring system based on the Internet of Things (IoT) using the ESP32 microcontroller and PZEM-004T sensor. The system allows real-time monitoring of electrical parameters such as voltage, current, power, and energy, with data displayed on digital devices like smartphones or computers.  Measurement data from the sensor is transmitted wirelessly to an IoT platform via Wi-Fi, enabling users to monitor electricity usage anytime and anywhere. A prototype method was used in this research, covering hardware and software design, sensor integration, and system testing.The testing results show that the system effectively provides accurate and responsive electricity usage data. With this system, users can identify usage patterns, detect high-power appliances, and make informed decisions to improve energy efficiency. The ability to access real-time data helps prevent energy waste and control monthly costs more effectively.Beyond individual benefits, this system also supports wider energy conservation initiatives by promoting conscious energy consumption behavior. The integration of IoT technology in household energy management demonstrates a practical solution for creating smarter and more sustainable living environments. This study confirms the potential of IoT-based systems to enhance energy awareness and support efforts in reducing overall electricity consumption.